Determining habitat quality for species that demonstrate dynamic habitat selection. Issue 23 (19th November 2015) - Beerens, James M.; Frederick, Peter C.; Noonburg, Erik G.; Gawlik, Dale E.
Abstract : Determining habitat quality for wildlife populations requires relating a species' habitat to their survival and reproduction. Here we establish an explicit link among changing resources, dynamic habitat selection, species abundance, and fitness for a predictive species distribution model that is used for short‐term water management and long‐term restoration planning. This study provides the first empirical evidence that dynamic habitat selection processes and distributions of wading birds over environmental gradients are linked with reproductive measures over periods of decades. Abstract: Determining habitat quality for wildlife populations requires relating a species' habitat to its survival and reproduction. Within a season, species occurrence and density can be disconnected from measures of habitat quality when resources are highly seasonal, unpredictable over time, and patchy. Here we establish an explicit link among dynamic selection of changing resources, spatio‐temporal species distributions, and fitness for predictive abundance and occurrence models that are used for short‐term water management and long‐term restoration planning. We used the wading bird distribution and evaluation models (WADEM) that estimate (1) daily changes in selection across resource gradients, (2) landscape abundance of flocks and individuals, (3) conspecific foraging aggregation, and (4) resource unit occurrence (at fixed 400 m cells) to quantify habitat quality and its consequences on reproduction for wetland indicator species. We linked maximum annual numbers of nests detected across the study area and nesting success of Great Egrets ( Ardea alba ), White Ibises ( Eudocimus albus ), and Wood Storks ( Mycteria americana) over a 20‐year period to estimated daily dynamics of food resources produced by WADEM over a 7490 km 2 area. For all species, increases in predicted species abundance in March and high abundance in April were strongly linked to breeding responses. Great Egret nesting effort and success were higher when birds also showed greater conspecific foraging aggregation. Synthesis and applications: This study provides the first empirical evidence that dynamic habitat selection processes and distributions of wading birds over environmental gradients are linked with reproductive measures over periods of decades. Further, predictor variables at a variety of temporal (daily‐multiannual) resolutions and spatial (400 m to regional) scales effectively explained variation in ecological processes that change habitat quality. The process used here allows managers to develop short‐ and long‐term conservation strategies that (1) consider flexible behavioral patterns and (2) are robust to environmental variation over time.